Study of the stirring speed for the biomass production of kefir grains - Arévalo, Fermín H. (2014)
The stirring speed required for the culture of kefir grains was studied, to optimize its growth in a culture medium of molasses and whey. The results show that this mixture of microorganisms requires stirring to optimize its growth and can grow in a wide range of stirring speeds, from laminar flow, with Reynolds number lower than 2000, to turbulent flow with Reynolds number greater than 3500. This shows that the culture of kéfir grains, can adapt to different stirring speeds, making its culture very easy with respect to this variable